Self-feeding molasses mixed with urea, phosphoric acid and water with or without ethyl alcohol to beef heifers. I. Feedlot and carcass study. - Richardson, D.; Smith, E.F.; Koch, B.A.; Cox, R.F. (Kansas Agricultural Experiment Station, 2011)
Phosphoric acid has been found to be an excellent source of phosphorus when used in beef cattle rations. Urea, a non-protein-nitrogen compound, has long been recognized as a satisfactory source of protein equivalent for ruminants. Recently, the idea has been advanced that small amounts of ethyl alcohol would be beneficial in ruminant rations. Because of the labor-saving aspect, the practice of self-feeding liquid supplements seems to appeal to many people. All of the above ingredients can be mixed easily and thoroughly with molasses. This test was conducted to study the value of self-feeding a mixture of molasses, urea, phosphoric acid and water with and without ethyl alcohol in the wintering and fattening ration of beef heifers.
Keywords: Beef; Molasses; Urea; Phosphoric acid; Carcass